Розробка метрологічного забезпечення контролю якості продукції машинобудування - Юношев, Д. Є. (ХНУРЕ, 2019)
Metrological control of smooth cylindrical joints has been improved. A comparative analysis of the existing normative base on the tolerances and landing of smooth cylindrical joints, calibre-scraps, calibre-plugs, methods of calculating the planting parameters, methods of statistical processing of measurement results is made. The proposed method of calculating calibers for controlling external elements of parts, providing interchangeability and quality of parts. The method of choice of universal means of measuring equipment for control of parameters of smooth cylindrical joints is offered.